Cyberbullying Perpetration Among Chinese Adolescents: The Role of Power Imbalance, Fun-seeking Tendency, and Attitude Toward Cyberbullying - Wang, Lin (Journal of interpersonal violence, 2022)
The imbalance of power affords individuals to bully others. However, limited studies have explored the specific aspects of power imbalance in predicting cyberbullying. Furthermore, a fun-seeking tendency as a motive for cyberbullying and attitudes toward cyberbullying as cognitive stimuli have rarely been studied in relation to mediating the associations between power imbalance and cyberbullying in an integrated framework. This study aims to narrow these research gaps. Multistage cluster random sampling was employed to recruit a total of 1103 adolescents (52.5% females) ranging in age from 12 to 18 years. Structural equation modeling analyses revealed that proficiency in technology use is not only directly and positively associated with cyberbullying but also indirectly associated with cyberbullying via fun-seeking tendency. Although social status among peers had no direct effect on cyberbullying, the indirect effects of social status among peers on cyberbullying via the fun-seeking tendency and attitude toward cyberbullying were significant. Notably, physical power was neither directly associated with cyberbullying nor through the fun-seeking tendency or attitude toward cyberbullying in associating with cyberbullying. Implications of these findings for developing effective interventions are discussed.